1999
DOI: 10.1111/j.1572-0241.1999.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pancreatic Cancer by Detecting Telomerase Activity in Pancreatic Juice: Comparison With K- Ras Mutations

Abstract: It was shown that the detection of telomerase activity in pancreatic juice is a more useful diagnostic tool for pancreatic cancer than that of K-ras mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 42 publications
0
27
1
Order By: Relevance
“…However, none of these tests demonstrated the requisite sensitivity and specificity to be useful as a general screening tool. The same is unfortunately true of a number of other potential targets, including hTert (telomerase catalytic subunit) (Uehara et al 1999), matrix metalloproteinase-2 (MMP-2) (Yokoyama et al 2002), and, more recently, aberrantly methylated promoter CpG islands of key genes (see, e.g., Fukushima et al 2002). Novel labeling and fractionation methods for pancreatic tissue (Chen et al 2005), serum proteins (Yu et al 2005), and secreted proteins (Gronborg et al 2006) coupled with tandem mass spectrometry have suggested additional candidate markers which await validation.…”
Section: Clinical Considerations In Pancreatic Cancermentioning
confidence: 99%
“…However, none of these tests demonstrated the requisite sensitivity and specificity to be useful as a general screening tool. The same is unfortunately true of a number of other potential targets, including hTert (telomerase catalytic subunit) (Uehara et al 1999), matrix metalloproteinase-2 (MMP-2) (Yokoyama et al 2002), and, more recently, aberrantly methylated promoter CpG islands of key genes (see, e.g., Fukushima et al 2002). Novel labeling and fractionation methods for pancreatic tissue (Chen et al 2005), serum proteins (Yu et al 2005), and secreted proteins (Gronborg et al 2006) coupled with tandem mass spectrometry have suggested additional candidate markers which await validation.…”
Section: Clinical Considerations In Pancreatic Cancermentioning
confidence: 99%
“…In pancreatic cancer, few molecularly characterised antigens have so far been available for use in vaccines. However, the catalytic subunit of telomerase, hTERT, expressed in 85 -90% of human cancer tissues (Vasef et al, 1999) and an attractive 'universal' tumour antigen (Autexier, 1999), is also expressed in pancreatic cancer where it has been used diagnostically (Suehara et al, 1998;Uehara et al, 1999). By turning on hTERT and telomerase activity, cancer cells are enabled to maintain functional telomeres at the end of chromosomes, and are prevented from going into senescence.…”
mentioning
confidence: 99%
“…Screening tests for the general population have to be accurate, safe, and convenient, as well as capable of high throughput. Many researchers have devoted considerable effort to discovering biomarkers of pancreatic cancer (8)(9)(10), and CA242 (11), M2-pyruvate kinase (12), PBF-4 (13), MIC-1 (14), PNA-binding glycoprotein (15), hTert (16), MMP-2 (17), and synuclein-g (18) have been reported as candidate biomarkers, but they were not clinically superior to CA19-9 or other clinical examinations.…”
Section: Introductionmentioning
confidence: 99%